Soil fauna trophic multifunctionality mediates the release of elements from decomposing typhoon‐generated leaf litter - Wang, Lifeng; See, Craig R.; Wang, Huibin; Cao, Rui; Liang, Guopeng; Zhang, Ajuan; Wang, Zhuang; Wang, Qin; Wang, Zhihui; Liu, Benjuan; Yang, Wanqin (Functional ecology, 2025)
Tropical cyclones (i.e. hurricanes, typhoons) cause large pulse fluxes of leaves that have not undergone senescence (i.e. green litter) to forest soils, with consequences for biogeochemical cycling. Energy and mineral nutrient concentrations of green litter are higher than the naturally senesced litter, likely affecting rates of decomposition and nutrient release, as well as the structure and composition of detrital food webs, but these effects have not been well quantified. During the typhoon ‘Hagubit’, we collected green and senesced litter from three common urban greening species, and then conducted a 316‐day field experiment to evaluate substrate quality affected the trophic multifunctionality of soil faunal communities and ultimately elemental release from the decomposing litter. Nitrogen (N), phosphorus (P), potassium (K), sodium (Na), calcium (Ca) and magnesium (Mg) were released at significantly higher rates from green litter than senesced litter. Aluminium (Al), manganese (Mn) and iron (Fe) displayed a net accumulation during litter decomposition, and the immobilization of these elements was significantly higher in green than senesced litter. Litter substrate chemistry directly affected the release rates of elements, but its influence was stronger in decomposing senesced litter compared to green litter. Detritivores dominated green and senesced litter faunal communities relative to predators, omnivores and herbivores, and these distinct fauna functional groups showed significantly positive correlation during decomposition, but soil fauna trophic multifunctionality was significantly higher in green litter and stimulated the release of elements. These findings suggest that typhoons dramatically alter the dynamics of nutrient release during litter decomposition, and the influences are mediated in part by its substrate quality and changes in soil fauna trophic multifunctionality, which has significant implications for the magnitude and timing of soil nutrient availability after typhoon disturbances. Read the free Plain Language Summary for this article on the Journal blog. Read the free Plain Language Summary for this article on the Journal blog.